THE LATIHAN METODE SATU REPETISI MAKSIMUM LEBIH EFEKTIF DARIPADA HOLD RELAX PADA INTERVENSI ULTRASOUD (US) DAN TRANSCUTANEOUS ELECTRICAL NERVE STIMULATION (TENS) DALAM MENURUNKAN NYERI OSTEOARTHRITIS GENU GRADE DUA - Ni Ketut Dewita Putri; I Made Niko Winaya; Ni Wayan Tianing (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2015)
Osteoarhtritis genu is a degenerative disease of the knee. The cartilage of the knee joint is damaged, which causes pain and functional limitations.The purpose of this study was to compare the effectiveness of one maximal repetition exercise, US, TENS with hold relax exercise, US, TENS in reducing pain of osteoarthritis genu grade two patients in Sanglah General Hospital Denpasar. This study was an experimental study with Pre and Post Test Control Group Design. Pain intensity was measured using Visual Analogue Scale (VAS). Hypothesis I and II were tested using paired sample t-test before and after the intervention in both groups, where the result obtained was p = 0.000 (p < 0.05). Data analysis result showed that interventions in both groups reduce pain significantly. Next, hypothesis III was tested using Independent T-test, where the result obtained was p = 0.000 (p < 0.05). This means that both groups have significant mean differences in the decrease of osteoarthritis genu grade two pain after given the interventions. Based on the mean decrease of pain percentage, the percentage was 38.39% and 19.15% in group 1 and group 2, respectively.In conclusion, the intervention given in group 1 (one maximal repetition exercise, US and TENS) reduces pain of osteoarthritis genu grade two more than the intervention given in group 2 (hold relax exercise, US and TENS).